2017
DOI: 10.1002/wsb.807
|View full text |Cite
|
Sign up to set email alerts
|

An aerial grid‐based sampling method to estimate nonbreeding duck abundance

Abstract: Probability-based sampling designs for aerial surveys are useful for estimating wintering waterfowl abundances in large areas with contiguous habitat (e.g., Mississippi Alluvial Valley). The effectiveness of these approaches for estimating abundance of nonbreeding waterfowl in small areas with discontinuous habitat has rarely been assessed. Surveys conducted within riverine areas introduce sampling design difficulties because of discontinuous bottomland habitat and irregularity of flooding events. Therefore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…An alternative is to base estimation on mark‐recapture distance sampling to remove residual heterogeneity resulting from distance between the animal and sampler. Hennig and Schoenecker (2023) found that mark‐recapture distance sampling was more cost‐effective and less invasive for aerial surveys of wild burros than methods that included a sample of telemetered animals (Hennig et al 2022), which are similar to what we have described and recommended here. Researchers should always be cognizant of heterogeneity in detection probability in the selection and implementation of the sampling method and analysis approaches for their data.…”
Section: Research Implicationssupporting
confidence: 73%
“…An alternative is to base estimation on mark‐recapture distance sampling to remove residual heterogeneity resulting from distance between the animal and sampler. Hennig and Schoenecker (2023) found that mark‐recapture distance sampling was more cost‐effective and less invasive for aerial surveys of wild burros than methods that included a sample of telemetered animals (Hennig et al 2022), which are similar to what we have described and recommended here. Researchers should always be cognizant of heterogeneity in detection probability in the selection and implementation of the sampling method and analysis approaches for their data.…”
Section: Research Implicationssupporting
confidence: 73%
“…Although we used a random selection protocol to select individuals on which to conduct behavior samples, ducks were not marked, therefore, it is possible that the same individual may have been sampled multiple times. However, this is unlikely because hundreds of thousands of ducks migrate through this region during spring (Hennig et al ) and generally ducks were in large flocks (mean = 64 individuals) so the probability of sampling the same bird twice, using our random selection protocol, was low.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has demonstrated that different wetland sampling strategies can influence population estimates from waterfowl surveys (Rutherford and Hayes 1973, Pearse et al 2009, Hennig et al 2017, highlighting the need to carefully investigate different sampling strategies when designing waterfowl surveys. Using individual wetlands as our sampling unit, we evaluated the influence of different sampling strategies on the accuracy and precision of breeding waterfowl abundance estimates in the Iowa PPR.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the Neyman sampling strategy consistently produced estimates that were not significantly different from predicted abundances for all species but were less precise than estimates from the other two sampling strategies. Other studies, primarily evaluating the influence of sampling strategies during winter waterfowl surveys, have also shown the value of optimal sampling strategies such as the Neyman strategy for obtaining accurate population estimates , Pearse et al 2009, Hennig et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation